Evaluation of the palatal split pattern in surgically rapid maxillary expansion—comparison of two techniques - Moura, Lucas Borin [UNESP]; Spin-Neto, Rubens; Sverzut, Cássio Edvard; Monnazzi, Marcelo da Silva [UNESP]; Trivellato, Alexandre Elias; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Springer Nature, 2016)
Purpose: Surgically assisted rapid maxillary expansion is performed to correct transverse deficiencies of the maxilla, and it is indicated in specific clinical situations. The literature presents different opinions in several aspects, mainly regarding the effect of disjunction of the pterygoid plates. The aim of this study was to evaluate the pattern of maxillary expansion obtained with two surgical techniques, with and without disjunction of the pterygoid plates. Methods: Twenty patients treated with surgically assisted rapid maxillary expansion for correction of transversal discrepancies were included in this retrospective study and divided into two groups: (G1) patients operated without disjunction of pterygoid plates and (G2) patients treated with release of the pterygoid plates. Results: There were seven male and 13 female patients, and the mean age was 29.9 years. Cone beam computed tomography images obtained after final activation of the expansion device were evaluated and complete disjunction of the midpalatal suture (type I) was present in 75 % of the patients whereas incomplete disjunction of the midpalatal suture (type II) was observed in 25 %. Chi-square test showed no statistically significant difference between groups (p = 0.606). Conclusion: No difference was found in relation to the maxillary disjunction pattern irrespective of the treatment given to pterygoid plates.
Keywords: Cranial sutures; Le Fort I osteotomy; Maxilla; Palatal expansion technique; SARME